Gender Violence in the Post-Patriarchalization of Global Age: A Comparative Perspective of Italy and Serbia - Bartholini, Ignazia; Jugović, Aleksandar (Zbornik Instituta za kriminološka i sociološka istraživanja, 2014)
The purpose of the essay is to overcome interpretative dualism between Italian and Serbian societies about gender violence against women. In a comparative approach, it will find elements of continuity between the decline of male domination in Italy and the decline of patriarchal power in Serbia as a result of a variety of historical and social causes that, inside the paper, are explained. The emancipation of women finds a block in the violence suffered by partners in some familiar contexts. While globalization and unemployment seem to deprive men of the marks of traditional power, but "men in decline" have a post-patriarchal "identity revanche" in assuming the dominant role of perpetrators in private life. Gender violence has an instrumental function within the relational dynamics. Also, gender violence has specific cultural, ethnic, and sexual characteristics in the reality of gender identity.